Coefficient Estimates for Two New Subclasses of Biunivalent Functions with respect to Symmetric Points. (25th February 2015) - Altınkaya, Şahsene; Yalçın, Sibel
Abstract : We introduce two subclasses of biunivalent functions and find estimates on the coefficientsa 2 anda 3 for functions in these new subclasses. Also, consequences of the results are pointed out.